A survey of ethnomedicinal plants used to treat cancer by traditional medicine practitioners in Zimbabwe - Patrick Rutendo Matowa; Mazuru Gundidza; Lovemore Gwanzura; Charles F. B. Nhachi (BMC, 2020)
Abstract Background Traditional medicine plays an important role in health care provision in the developing world. A number of cancer patients have been found to be using traditional medicine as primary therapy and/or as complementary medicine. Cancer is one of the leading causes of morbidity and mortality globally among the non-communicable diseases. The aim of this study was to identify the plants used by traditional medicine practitioners (TMPs) in Zimbabwe to treat cancer. Methods A structured questionnaire was used to interview consenting registered TMPs on ethnomedicinal plants they use to treat cancer. A review of published literature on the cited plants was also carried out. The practitioners were asked about the plants that they use to treat cancer, the plant parts used, type of cancer treated, other medicinal uses of the plants and preparation and administration of the plant parts. Results Twenty (20) TMPs took part in the study. A total of 18 medicinal plant species were cited. The commonly treated types of cancer were breast, prostate, colon, skin and blood cancers with most plants being used to treat skin, blood and breast cancers, respectively. Of the medicinal plants cited, 44.4% were used to treat all cancer types. The most used plant parts were the roots (72.2%) and leaves (72.2%) followed by the bark (38.9%). The medicinal plants were used for multiple ailments. The most common plant preparation methods were infusion (72.2%) and decoction (66.7%) and the oral route of administration, as extracts and powder put in tea and porridge, was the most used. Conclusion The frequently used plant parts were leaves and roots. The traditional uses of the medicinal plants cited in this study resonate well with their reported uses from other ethnopharmacological studies done in other parts of the world. The plants used by TMPs to treat cancer in Zimbabwe, if adequately explored, can be instrumental in the discovery and development of cancer drugs.